Nora’s Re-birth as a Human: A Critical Analysis of Ibsen’s A Doll’s House - Jassim Ali Al-Zubaidi, Azhar (Journal of College of Education, 2022)
AbstractThis paper scrutinizes Henrik Ibsen’s A Doll’s House where the female protagonist character is analyzed through investigation of the three elements of human beings: soul, body, and mind. This analysis of the play is processed along with the analysis of the dramatic elements, techniques, and conventions of dramatic criticism. The investigation of the stages of social drama in the female character’s situation as presented in this play is intended to highlight woman’s tragedy in patriarchal society. Ibsen sees women caught in a tragic situation where Nora is found in confrontation with society and its patriarchal concepts. This paper, thus, traces women’s attempts to challenge gender inequality as presented through the female protagonist’s acts. The female character actions in incidents of stereotyping, objectification, and oppression which reflect gender politics, sexuality, and power relations, should reveal her stand facing gender inequality under patriarchy. Evidence in the play text that demonstrate the female character’s negotiation, rejection, and/or objection to all that deprives her equal rights to those of man as human should reveal to which extent, she manages to challenge gender inequality. By so doing Nora breaks the inferior status imposed on her being a woman.
Keywords: Patriarchy; stereotyping; objectification